Schulzinger, U.S. Diplomacy Since 1900 - Redinger, Matthew (Teaching History: A Journal of Methods, 2000)
Robert Schulzinger has done it again. In this, the fourth edition of his survey of United States diplomacy in the twentieth century, he has provided a text remarkable in its combination of breadth and readability. In this book's tightly packed sixteen chapters, Schulzinger manages to provide a classic account of United States foreign relations since the tum of the century.